Israel in the Iron-Smelting Furnace? Towards a New Understanding of the כּוּר הַבַּרְזֶל in Deut 4:20 - Vang, Carsten (HIPHIL Novum, 2014)
Most scholars interpret the metallurgical imagery of כּוּר הַבַּרְזֶל in Deut 4:20 and parallels as a reference to an iron-smelting furnace describing the harsh realities of Israel's slavery in Egypt. A consideration of the Hebrew mode of expression however leads to the conclusion that the metaphor refers to a crucible made of the hardest metal generally known in antiquity, which is iron. The metaphor therefore conveys the impression that the Israelite existence in Egypt is described like being trapped in a crucible made of a hard and impenetrable material that cannot be broken. This article also argues that Deut 4:20 appears to be the provenance of the parallel phraseology of 1 Kong 8:51 and Jer 11:4.